Physalin H, physalin B, and isophysalin B suppress the quorum-sensing function of Staphylococcus aureus by binding to AgrA - Yamaguchi, Junpei; Manome, Teruhisa; Hara, Yasumasa; Yamazaki, Yuriko; Nakamura, Yuumi; Ishibashi, Masami; Takaya, Akiko (Frontiers in Pharmacology, 2024)
The virulence of Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA), depends on the expression of toxins and virulence factors controlled by the quorum-sensing (QS) system, encoded on the virulence accessory gene regulator (agr) locus. The aim of this study was to identify a phytochemical that inhibits Agr-QS function and to elucidate its mechanism. We screened 577 compounds and identified physalin H, physalin B, and isophysalin B—–phytochemicals belonging to physalins found in plants of the Solanaceae family—–as novel Agr-QS modulators. Biological analyses and in vitro protein–DNA binding assays suggested that these physalins suppress gene expression related to the Agr-QS system by inhibiting binding of the key response regulator AgrA to the agr promoters, reducing the function of hemolytic toxins downstream of these genes in MRSA. Furthermore, although physalin F suppressed gene expression in the Agr-QS system, its anti-hemolytic activity was lower than that of physalins H, B, and isophysalin B. Conversely, five physalins isolated from the same plant with the ability to suppress Agr-QS did not reduce bacterial Agr-QS activity but inhibited AgrA binding to DNA in vitro. A docking simulation revealed that physalin interacts with the DNA-binding site of AgrA in three docking states. The carbonyl oxygens at C-1 and C-18 of physalins, which can suppress Agr-QS, were directed to residues N201 and R198 of AgrA, respectively, whereas these carbonyl oxygens of physalins, without Agr-QS suppression activity, were oriented in different directions. Next, 100-ns molecular dynamics simulations revealed that the hydrogen bond formed between the carbonyl oxygen at C-15 of physalins and L186 of AgrA functions as an anchor, sustaining the interaction between the carbonyl oxygen at C-1 of physalins and N201 of AgrA. Thus, these results suggest that physalin H, physalin B, and isophysalin B inhibit the interaction of AgrA with the agr promoters by binding to the DNA-binding site of AgrA, suppressing the Agr-QS function of S. aureus. Physalins that suppress the Agr-QS function are proposed as potential lead compounds in the anti-virulence strategy for MRSA infections.